Toward a Southern criminology - Zaffaroni, Eugenio Raúl (Southernising criminology, 2024)
This chapter offers a historical reconstruction of the relations between colonialism, criminological knowledge, and punitive power. It poses that Southern criminology is eminently critical, because it develops in a context of irrational use of punitive power. Then, the piece moves on to show the current faces of colonialism - including its late financial version – and the need for an integrated methodology, in order to overcome the violations of human rights happening in the South.